Using Financial Ratios in Predicting the Crises of Libyan Commercial Banks. - الفرجاني د. إبراهيم مسعود; الصديق أ. نور الدين ناصر (Dirasat in Economics and Business, 2021)
This research aims to use financial ratios in predicting the crises of Libyan commercial ba-nks during the period (2009-2018). To achieve this and to cover all aspects of the research, the descriptive approach was relied on, with its documentary entries, to search for sources in the field of financial ratios, for-ecasting banking crises, and the quantitative approach to calcu-lating financial ratios to predict bank failures, Calculating the horizontal analysis of the fina-ncial ratios to find out the rise or fall in the financial ratios over time to reach the search results.The research was applied to (Al Wahda Bank, Sahara Bank, Al Jumhuria Bank, Nation- al Commercial Bank), due to the availability of data on these banks in the period specified for the research and their large size according to capital, assets,de-posits, credit and the oldest established.The research showed a set of results, the most important of which is that the commercial banks in question have sufficient liquidity, sufficient capital, good operating efficiency, and adeq-uate asset quality, while they suffer from a decrease in profi-tability and an increase in credit risk, which may cause a future banking crisis.The research recommended a set of recommendations, the mo-st important of which are main-taining an appropriate level of liquidity, balancing liquidity and profitability, and raising the ban-k's profitability by diversifying investments and reducing credit risks by managing credit well.